Milestones in the History of the Metabolic Management of Hyperglycemia in Pregnancy - de Leiva-Pérez, Alejandra; Brugués, Eulàlia; de Leiva-Hidalgo, Alberto (Unveiling Diabetes - Historical Milestones in Diabetology, 2020)
This chapter reviews significant milestones in the history of the metabolic management of hyperglycemia in pregnancy. During the pre-insulin era, women with diabetes rarely became pregnant, and when they did, the prognosis for both mother and child was most unfavorable. The cornerstone of diabetes management before the introduction of insulin was dietary therapy. The introduction of insulin into clinical use, the increased understanding of the etiopathology of diabetes and pregnancy, the developments in metabolic and obstetric management, and major advances in technology have led to significant improvements in pregnancy outcomes. The pioneers in this field include, among others, Priscilla White, Jørgen Pedersen, Norbert Freinkel, and Lois Jovanovic, and their main contributions are reviewed here. Different technologies for management are also described. The idea of gestational diabetes as a clinical entity was disputed for many years. Even nowadays, the screening and diagnostic criteria are controversial subjects. Gestational diabetes is increasing worldwide, parallel to the epidemic of obesity and type 2 diabetes. Recently, evidence has emerged that in utero exposure to hyperglycemia increases the risk to the offspring of developing obesity and disorders of glucose metabolism in the future, thus perpetuating the cycle of metabolic disorders between mother and child.